The Catholic Church in Conflict with State Power: an Analysis of Historical Literature Studies on the Relationship Between Church and State in Medieval Europe - Elisabeth Stevani G; Anita Syamsinar; Hafiz Zuhdi; Edi Putra Rasmamana PA; Pujiati, Pujiati (Jurnal Multidisiplin Sahombu, 2026)
The relationship between the Catholic Church and state power in medieval Europe represents one of the most complex dynamics in Western political and religious history. During this period, the Church functioned not only as a spiritual institution but also as a powerful social, political, and economic force. Conflicts between the Church and the state frequently arose due to overlapping authorities, particularly concerning legitimacy of power, appointment of church officials, land ownership, and interpretations of law and morality. This study aims to analyze the forms of conflict between the Catholic Church and state authorities in medieval Europe and the factors underlying these tensions. The research employs a literature study method by examining various historical sources, including classical historical texts and relevant contemporary scholarly works. The findings indicate that Church–state conflicts were not merely theological but also political and economic in nature. Struggles between the papacy and European monarchs, such as the Investiture Controversy, reflect competition for influence over society and power structures. This study is expected to contribute to a deeper understanding of the historical roots of Church–state relations and their relevance to the development of modern concepts of separation of powers.